Citizen participation in resilient society: historical insights and monitoring trends of the EU’s policy and institutions - Olimid, Anca Parmena (Society Register, 2023)
Resilient society and social dialogue are core topics for monitoring citizens’ initiative in participatory democracy as an engaged citizen often empowers governance facilitating active social engagement and democratic. (1) Background: The intent of the current research is to document and monitor the notion of “resilient society” and twenty associated topics in order to provide the latest emerging illustrations of the impact of social media on citizens’ initiative and participation levels in the European Union (EU); (2) Methods: Based on the Brand24 media monitoring tool, the quantitative and qualitative analysis of the social media reach focuses a period of one month (June-July 2023) with the aim to assess a better understanding of the resilient society and citizens’ participation; (3) Results and findings: The results of the research emphasize the role of citizens’ engagement and social dialogue for a resilient society by scaling the linkages between the historical, institutional and participative levels; (4) Discussion: The article shows how policy agenda and decisions, historical facts and social realities influence the social media reach and highlights the outcomes of the sentiment analysis and influence score of the selected topics.